The concepts and the essence of non-conventional agricultural land use, its environmental friendliness and capitalization - Tretiak, V.; Lyashynskyy, V. (Land Management, Cadastre and Land Monitoring, 2019)
In this article the concepts and essential features of non-conventional agricultural land use have been defined. The main economic and land management actions were designated to ensure the greening and capitalization of non-conventional agricultural land use. In modern economic science, the terms "organic farming" and "non-conventional farming" are often used at the same time and often equated. However, in our opinion, there are a number of differences between them, so it is necessary to harmonize the interpretation of relevant concepts and categories. Non-conventional land use should be understood as the process of organizing economically efficient, environmentally friendly and socially-oriented use of agricultural land as means of basic production in close interaction with the environment, and with land ownership relations (where human and its intellect are the key to the formation of land capital). Key aspects of the essence of non-conventional land use are its greening and capitalization. This can be provided by the following means: studying of the land and soil suitability for growing, for example, niche crops, within the land use; working out different options for the non-conventional land use development; land management options development and implementation of land improvements; developing a forecast for the economic efficiency of land use; deciding on the feasibility of organizing non-conventional land use; development of an economic management plan for the organization of non-conventional land use. Keywords. non-conventional agricultural land use, niche crops, non-conventional farming, land use greening, land use capitalization.